Axillary Brachial Plexus Block - Ashish R. Satapathy; David M. Coventry (Anesthesiology Research and Practice)
The axillary approach to brachial plexus blockade provides satisfactory anaesthesia for elbow, forearm, and hand surgery and also provides reliable cutaneous anaesthesia of the inner upper arm including the medial cutaneous nerve of arm and intercostobrachial nerve, areas often missed with other approaches. In addition, the axillary approach remains the safest of the four main options, as it does not risk blockade of the phrenic nerve, nor does it have the potential to cause pneumothorax, making it an ideal option for day case surgery. Historically, single-injection techniques have not provided reliable blockade in the musculocutaneous and radial nerve territories, but success rates have greatly improved with multiple-injection techniques whether using nerve stimulation or ultrasound guidance. Complete, reliable, rapid, and safe blockade of the arm is now achievable, and the paper summarizes the current position with particular reference to ultrasound guidance.